2020
DOI: 10.1002/nop2.501
|View full text |Cite
|
Sign up to set email alerts
|

Ethical competence in a profession: Healthcare professionals' views

Abstract: Aim Ethical competence is a crucial component for enabling good quality care but there is insufficient qualitative research on healthcare professionals' views on ethical competence. The aim of this study was to investigate healthcare professionals' views on ethical competence in a student healthcare context. Design A qualitative design and a hermeneutical approach were used. Methods The material consists of texts from interviews with healthcare professionals (N = 10) in a student healthcare context. The method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 49 publications
1
10
0
1
Order By: Relevance
“…That could explain why educators in profile C evaluated their competence as lower than the other two profiles. Although educators holding a doctoral degree are experts in research and produce new knowledge to support clinical decision-making [51,60], previous research has shown that the development of ethical and cultural competence also requires practical experience [24,56,61].…”
Section: Discussionmentioning
confidence: 99%
“…That could explain why educators in profile C evaluated their competence as lower than the other two profiles. Although educators holding a doctoral degree are experts in research and produce new knowledge to support clinical decision-making [51,60], previous research has shown that the development of ethical and cultural competence also requires practical experience [24,56,61].…”
Section: Discussionmentioning
confidence: 99%
“…It helps obstetricians and gynecologists (OB/GYNs) find better solutions or alternative solutions whenever needed for the patients. Ethical competence improves the doctor-patient relationship [1]. In the early 1970s, the terms "fetal patient" and "fetus as a patient" entered the medical literature, signifying the importance of applying practice ethics to the fetus as well.…”
Section: Introductionmentioning
confidence: 99%
“…Ethical issues and dilemmas occur in all forms of research when human participants are involved [ 11 ] and this is no less the case within ANH research. Ethical competence is the capacity that researchers need to possess to identify those dilemmas and ethically handle them [ 12 – 14 ] and such competence is also a crucial factor that enables researchers to resolve ethical dilemmas, make value-based decisions and implement ethically sustainable good research practices [ 15 ]. It is important to raise and improve ethical awareness, the acquisition of ethical knowledge, and support reflection on professional practice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%